Wheat improvement for heat and drought stress tolerance - Giri, Anju (Kansas State University, 2019)
Heat and drought are the major abiotic factors that limit wheat production worldwide. Wheat is one of the important staple crops, so, the production decline due to these factors faces a major challenge in addressing food security. Grain filling in wheat occurs when the temperature is rising, and soil moisture is declining in most wheat growing environment, so there is high demand in breeding wheat for post anthesis heat and drought stress tolerance. However, limited genetic variability in wheat cultivars possess a challenge. The objective of the first study was to screen wild emmer wheat (Triticum dicoccoides) for post anthesis heat tolerance and measure physiological traits and yield trait associated with the tolerance. Twenty-one accessions of Triticum dicoccoides and four check varieties were screened at optimum temperature (25/19 °C day/night) and high temperature (35/29 °C day/night). High temperature decreased flag leaf survival duration, chlorophyll content, and chlorophyll fluorescence more in the wild accessions than in the checks. A few wild accessions were found to be heat tolerant based on the lower heat susceptibility index (HSI) value in seed weight. Therefore, there is a potential for utilizing this genetic variability from the accessions to improve post anthesis heat tolerance in wheat. The maintenance in seed weight might be coming from the mobilization of stored reserve in the stem. The stem reserves are commonly called water-soluble carbohydrates (WSC). WSC accumulated during the vegetative stage, pre-flowering, or right after flowering can be mobilized to assist grain filling when assimilate supply is limited under stress. The second chapter is about the physiological and genetic basis of water-soluble carbohydrates (WSC) concentration during mid- grainfilling stage in wheat. We evaluated 400 diverse winter wheat breeding lines and 30 released varieties in different environments ranging from irrigated to rainfed for WSC concentration. WSC concentration was significantly and positively correlated with the seed weight, whereas the height was mostly negatively correlated, and we didn’t see any relation with heading date. Less decline in grain yield under simulated terminal drought stress was observed in varieties with high WSC content. Further, we identified six significant SNP markers in 7D region significantly associated with the WSC concentration, and each marker explained 4-5% of the variation. On running several genomic selection prediction models on WSC using ridge regression, partial least squares, elastic net, and random forest models and different training population sizes (20%, 40%, 60%, and 80%), the prediction accuracy increased from 0.2 to 0.6. The accuracy increased as a large amount of data was available to train the model, and overall the highest accuracy was observed with the random forest and average of all four models. The accuracy can be further increased with the inclusion of a large number of samples, and multi- year and location testing on WSC. Higher genetic variation, high heritability, and significant positive relation with seed weight make WSC an important trait for selection under post anthesis drought. In the third study, aerial phenotyping using UAV with a multispectral camera was used to capture the images in three different wave bands: red, green, and near infrared. Normalized Difference Vegetative Index (NDVI) was calculated from red and near infrared bands. NDVI calculated from the aerial imaging during reproductive stages were more correlated with the grain yield than a visual screening of percentage greenness. NDVI measurement during grain filling had the highest significant correlation and explained more than 50% variation in the yield. Lodging was another factor impacting yield explaining about 60% variability in yield. With its wide applicability, aerial phenotyping has the potential for assisting breeders in selecting diverse genotypes and can outperform visual selection.
Keywords: Wheat; Heat-stress; NDVI; Water-soluble carbohydrates; Genomic selection; Drought